17β-estradiol prevents experimentally-induced oxidative damage to membrane lipids and nuclear DNA in porcine ovary. (2nd January 2016) - Stepniak, Jan; Karbownik-Lewinska, Malgorzata
Abstract: Estrogens, with their principle representative 17β-estradiol, contribute to the redox state of cells showing both pro- and antioxidative properties. In the ovary, being the main source of estrogens, maintaining balance between the production and detoxification of ROS is crucial. Whereas ovary estrogen concentration is difficult to estimate, its circulating concentration in women may reach the nanomolar level. The aim of the study was to evaluate the effects of 17β-estradiol on oxidative damage to membrane lipids (lipid peroxidation, LPO) and to nuclear DNA in the porcine ovary under basal conditions and in the presence of Fenton reaction (Fe 2+ +H2 O2 →Fe 3+ + OH + OH − ) substrates. Ovary homogenates and DNA were incubated in the presence of 17β-estradiol (1 mM–1 pM), without/with FeSO4 (30 μM) + H2 O2 (0.5 mM). Malondialdehyde + 4-hydroxyalkenals (MDA + 4-HDA) concentration (LPO index) was measured spectrophotometrically. The concentration of 8-oxo-7, 8-dihydro-2'-deoxyguanosine (8-oxodG) (DNA damage index) was measured by HPLC. We observed that 17β-estradiol did not alter the basal level of oxidative damage, but reduced Fe 2+ +H2 O2 -induced oxidative damage to membrane lipids when ≥10 nM and to DNA at concentrations ≥1 nM. In the ovary at near physiological concentration, 17β-estradiol prevents experimentally induced oxidative damage. This suggests that under physiological conditions this hormone may contribute to protecting the ovary against oxidative damage.